Shoot tip culture for the propagation, conservation and exchange of Musa germplasm - Vuylsteke, D.R. (1989)
This publication reviews in detail the history of shoot-tip culture of Musa, in vitro propagation procedures, in vitro conservation, germplasm exchange using in vitro cultures and potential problems.